Mediating Broad Band Light Trapping in Silicon Solar Cell by Aluminum Nanoparticles with Native Oxide Shell. (2017) - Parashar, Piyush K.; Sharma, R.P.; Komarala, Vamsi K.
Abstract: We have investigated the role of a native oxide layer on aluminum nanoparticles (Al NPs) in the light forward scattering into the silicon, with the aim of enhancing silicon solar cell performance. Initially, the NPs' morphology optimized for maximum light confinement into the silicon wafer. Oxide layer inclusion of 2.2 nm on Al NPs' surface reduces the reflectance (from ∼25% to ∼21%), and improves the photocurrent enhancement (from ∼27 to ∼30 mA/cm 2 ) due to the better light forward scattering, and reduced parasitic absorption losses, with no occurrence of Fano resonances. Oxide layer growth effect around NPs also calculated using the Bruggeman effective medium theory. A finite-element method is adapted to calculate the peak radiative power, spectral field distributions, and spatial dipole field distributions for experimentally optimized Al NPs size on a silicon substrate for explaining plasmonic device performance enhancement in the localized surface plasmon resonance, and off-resonance regions.